Single-Nucleotide Variants in the AIM2 – Absent in Melanoma 2 Gene (rs1103577) Associated With Protection for Tuberculosis - Figueira, Mariana Brasil de Andrade; de Lima, Dhêmerson Souza; Boechat, Antonio Luiz; Filho, Milton Gomes do Nascimento; Antunes, Irineide Assumpção; Matsuda, Joycenéa da Silva; Ribeiro, Thaís Rodrigues de Albuquerque; Felix, Luana Sousa; Gonçalves, Ariane Senna Fonseca; da Costa, Allyson Guimarães; Ramasawmy, Rajendranath; Pontillo, Alessandra; et al. (Frontiers in Immunology, 2021)
Tuberculosis (TB) remains a serious public health burden worldwide. TB is an infectious disease caused by the Mycobacterium tuberculosis Complex. Innate immune response is critical for controlling mycobacterial infection. NOD-like receptor pyrin domain containing 3/ absent in melanoma2 (NLRP3/AIM2) inflammasomes are suggested to play an important role in TB. NLRP3/AIM2 mediate the release of pro-inflammatory cytokines IL-1B and IL-18 to control M. tuberculosis infection. Variants of genes involved in inflammasomes may contribute to elucidation of host immune responses to TB infection. The present study evaluated single-nucleotide variants (SNVs) in inflammasome genes AIM2 (rs1103577), CARD8 (rs2009373), and CTSB (rs1692816) in 401 patients with pulmonary TB (PTB), 133 patients with extrapulmonary TB (EPTB), and 366 healthy control (HC) subjects with no history of TB residing in the Amazonas state. Quantitative Real Time PCR was performed for allelic discrimination. The SNV of AIM2 (rs1103577) is associated with protection for PTB (padj: 0.033, ORadj: 0.69, 95% CI: 0.49-0.97). CTSB (rs1692816) is associated with reduced risk for EPTB when compared with PTB (padj: 0.034, ORadj: 0.50, 95% CI: 0.27-0.94). Serum IL-1B concentrations were higher in patients with PTB than those in HCs (p = 0,0003). The SNV rs1103577 of AIM2 appeared to influence IL-1 release. In a dominant model, individuals with the CC genotype (mean 3.78 ± SD 0.81) appeared to have a higher level of IL-1B compared to carriers of the T allele (mean 3.45 ± SD 0.84) among the patients with PTB (p = 0,0040). We found that SNVs of AIM2 and CTSB were associated with TB, and the mechanisms involved in this process require further study.